2005
DOI: 10.1158/1078-0432.ccr-04-2088
|View full text |Cite
|
Sign up to set email alerts
|

Histone Deacetylase Inhibitors Radiosensitize Human Melanoma Cells by Suppressing DNA Repair Activity

Abstract: Purpose: Histone deacetylase (HDAC) inhibitors have emerged recently as promising anticancer agents. They arrest cells in the cell cycle and induce differentiation and cell death. The antitumor activity of HDAC inhibitors has been linked to their ability to induce gene expression through acetylation of histone and nonhistone proteins. However, it has recently been suggested that HDAC inhibitors may also enhance the activity of other cancer therapeutics, including radiotherapy. The purpose of this study was to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
288
2
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 315 publications
(308 citation statements)
references
References 50 publications
15
288
2
3
Order By: Relevance
“…It is established that the g-H2AX form of the histone has an important role in recruiting repair factors to nuclear foci following induction of DSBs (Paull et al, 2000;Celeste et al, 2003;Olive and Banath, 2004). Recent studies have shown that incubation of cells with HDAC inhibitors including MS-275 and sodium butyrate, results in prolonged expression of induced g-H2AX foci (Camphausen et al, 2004a;Munshi et al, 2005). These findings indicate that HDAC inhibitor-mediated radiosensitization is associated with a decrease in the repair of DSBs.…”
Section: Mechanisms Of Hdac Inhibitor-mediated Enhanced Radiation Senmentioning
confidence: 96%
See 3 more Smart Citations
“…It is established that the g-H2AX form of the histone has an important role in recruiting repair factors to nuclear foci following induction of DSBs (Paull et al, 2000;Celeste et al, 2003;Olive and Banath, 2004). Recent studies have shown that incubation of cells with HDAC inhibitors including MS-275 and sodium butyrate, results in prolonged expression of induced g-H2AX foci (Camphausen et al, 2004a;Munshi et al, 2005). These findings indicate that HDAC inhibitor-mediated radiosensitization is associated with a decrease in the repair of DSBs.…”
Section: Mechanisms Of Hdac Inhibitor-mediated Enhanced Radiation Senmentioning
confidence: 96%
“…For example, it has been shown that the radiation-induced increase in Rad51 and DNA-PKcs expression is markedly attenuated by pretreatment of a human prostate cancer cell-line with SAHA (Chinnaiyan et al, 2005). Similarly, another study has demonstrated that sodium butyrate decreases the expression of critical DNA repair proteins Ku70, Ku86 and DNA-PKcs in two melanoma cell-lines (Munshi et al, 2005).…”
Section: Mechanisms Of Hdac Inhibitor-mediated Enhanced Radiation Senmentioning
confidence: 99%
See 2 more Smart Citations
“…The 18 human HDACs may be classified as either zinc-or NAD 1 -dependent and further subclassified into class I (HDAC1, 2, 3, and 8), class II (HDAC4, 5, 6, 7, 9, and 10), class III (including NAD 1 -dependent sirtuins), and class IV (HDAC11) HDACs. As HDACs regulate a wide variety of processes involved in carcinogenesis, multiple mechanisms may explain the clinical activity of HDAC inhibitors [249,250], including altered gene expression of cell-cycle and apoptotic regulatory proteins [251][252][253][254][255], acetylation of nonhistone proteins regulating cell growth and survival [256][257][258][259], angiogenesis [260,261], aggresome formation [262], and DNA repair [263]. In addition, HDAC inhibitors may have important effects on the tumor microenvironment via reactive oxygen species [264,265], enhanced antigen presentation [266] and downregulation of immunomodulatory cytokines, like IL-10 [267].…”
Section: Hdac Inhibitorsmentioning
confidence: 99%